Board Characteristics, Audit Committees and Earnings quality - Jiao, Xuelin (2017)
This paper examines the relations among board characteristics, audit committees and earnings quality. It emphasizes the role of strong internal corporate governance mechanisms in improving the earnings quality. Five characteristics are chosen to represent the internal corporate governance structure: board size, board independence, CEO duality, audit size and audit independence. The abnormal accruals are calculated by the Jones (1991) Model as the measure of earnings quality．Based on a sample of 77 non-financial UK firms out of FTSE100 from the year 2012 to 2016, a highly proportion of independent directors on the board is found to be significantly associated with a high level of earnings quality. The independence of audit committee is also positively related to earnings quality. However, no evidences prove that board size, CEO duality and audit size have effects on earnings quality.